2017
DOI: 10.1037/rep0000155
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature on pediatric concussions and return-to-learn (RTL): Implications for RTL policy, research, and practice.

Abstract: Given the inconsistencies in RTL literature, more rigorous research is needed to inform concussion policy and practice to assist with pediatric concussion management. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 68 publications
0
36
0
Order By: Relevance
“…Two summary statements provided evidence for the time between stages in RTA/RTS protocols,4 29 and one descriptive study reported the probability of complete RTA in adolescent athletes with concussion 30. The RTA/RTS protocols created by the CanChild group provide recommendations on the time between stages 25 31…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two summary statements provided evidence for the time between stages in RTA/RTS protocols,4 29 and one descriptive study reported the probability of complete RTA in adolescent athletes with concussion 30. The RTA/RTS protocols created by the CanChild group provide recommendations on the time between stages 25 31…”
Section: Resultsmentioning
confidence: 99%
“…The time between stages in RTA/RTS protocols should be a minimum of 24 hours to ensure there is no symptom exacerbation before beginning the next stage 4 29. The updated CanChild RTA/RTS protocols recommend that children take a minimum 24 hours between steps 26 31.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SRC can induce changes in attention, cognitive processing speed, learning, short-term memory and executive function that make learning difficult 87. Return to learn is the process of transitioning back to the classroom following concussion using individualised academic adjustments87 88 (see table 4).…”
Section: Management Of Concussionmentioning
confidence: 99%